(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Plants are exposed during their development to the influence of various stressful factors, both abiotic and biotic in natural conditions of habitation. Thermal stress is likely the most important abiotic factor that adversely affects plant growth and development. Wheat (Triticum aestivum L.) is one of the most economically important crops worldwide. In this study, three Latvian winter wheat cultivars ´Creator´, ´Galerist´, and ´Skagen´ were used as a research model that were subjected to short-term high temperature (42°C, 1 h) and analyzed for the following growth parameters (maximum length of root, length of first leaf and coleoptile as well as seedlings weight). In general, short-term high temperature caused an insignificant reduction in almost all growth criteria like the first leaf growth, coleoptile growth, seedlings weight, and maximal root growth in wheat cultivars ´Skagen´ and ´Galerist´ at the 6th day of development. Furthermore, almost all growth characteristics were stimulated by short-term high temperature in the wheat cultivar ´Creator´. A slowing of the growth processes under the influence of short-term thermal stress revealed varietal specificity on the impact of this stressor on the morphological structure of cereal, which makes it possible to diagnose the stress tolerance of wheat cultivars.